Trehalose and a calcium chelator for ram semen cryopreservation - Bittencourt, Rodrigo Freitas (2014)
Twenty semen samples from ten rams of the Santa Inês breed were cryopreserved with the goal of verifying the effect of trehalose addition (100mOsmol) (group 1 -TRIS+TRE) to a Tris-egg yolk-glycerol extender (group 2 -TRIS), associated or not to the calcium chelator EDTA (group 3 -TRIS+TRE+EDTA), on the post-thaw sperm viability. After evaluation, the diluted semen samples were cooled at 5C and frozen in liquid nitrogen steam. After thawing, the kinetic sperm parameters were analyzed by a computer analyses system (CASA). The sperm viability was observed by using the multiple sperm parameter staining with propidium iodide (PMI, plasmatic membrane integrity), JC-1 (MMP, mitochondrialmembrane potential) and FITC-PSA (ACI, acrosomal integrity). The statistical analysis was performed using the SAS software, applying the MEANS procedure for descriptive analysis and the GLM procedure with the Student-Newman-Keuls test (SNK) for comparisonof sperm parameters among different groups(with P<0.05). The percentage of total and progressive motility post-thaw were the greatest (P<0.05) for the TRIS group in relation to trehalose ones. The PMI, MMP, and ACI rates (%) did not present differences (P>0.05) among the groups. It can be concluded that the trehalose addition to the TRIS extender, associated or not to EDTA, had detrimental effect on cryosurvivalram sperm.